Prevalensi dan Faktor Risiko yang Berhubungan dengan Keluhan Computer Vision Syndrome pada Siswa Selama Pandemi COVID-19: Research - -, Erfira; Nuryasin, Muhammad Farras; Hermawati, Luluk; Irawati, Nur Bebi Ulfah (Cermin Dunia Kedokteran, 2026)
Introduction: The COVID-19 pandemic has led to major changes in the education system through the implementation of the school-from-home policy since March 16, 2020. This condition led to a significant increase in the intensity of gadget use among students, potentially triggering eye health problems such as computer vision syndrome (CVS). This study aimed to determine the prevalence of CVS and the factors influencing its occurrence among students at a private senior high school in Central Jakarta during the online learning period. Methods: A cross-sectional study using random sampling was conducted, and data were collected via online questionnaires completed by students. Results: Out of a total of 166 respondents, 74.7% of students experienced CVS symptoms. The most commonly reported complaints included itchy eyes (78.9%), watery eyes (69.3%), and headaches (63.9%). Most of these complaints were associated with prolonged gadget use, namely, more than 6 hours per day. Conclusion: The duration of digital device use during online learning and refractive error were important factors contributing to the prevalence of CVS among students. Promotive and preventive efforts are needed to reduce the risk of CVS through education on healthy gadget use during distance learning.